The Influence of Product Quality and Brand Image on Purchasing Decisions of Carvil Sandals at Hypermart Cyberpark Karawaci - Jakariah Jakariah (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
The purpose of this study was to determine the effect of product quality and brand image on the purchasing decision of Carvil sandals at Hypermart Cyberpark Karawaci. This research method is quantitative associative type. This study uses an instrumen test analysis technique, which consists of validity and reliability, classical assumption test analysis and quantitative analysis test. The results showed that there was a partial effect of product quality on the purchasing decision of Carvil sandals at Hypermart Cyberpark Karawaci, seen from the results of the t test (partial test) which showed the t value of 5,751 > ttable of 1,985 and a significant value of 0,00 < 0,05. Then there is the influence of brand image on the decision to buy Carvil sandals at Hypermart Cyberpark Karawaci partially, seen from the results of the t test (partial test) tcount 4,104 > ttable 1,985 and significant value 0,00 < 0,05. Meanwhile, based on the F test (simultaneous test) shows that there is an effect of product quality and brand image on the decision to buy Carvil sandals at Hypermart Cyberpark Karawaci in a simulant manner, seen from the results of the F test (simultaneous test) which shows thecalculated 249,300 > Ftable 2,700 and significant value of 0,000 <0,05. The results of the determination test show the Adjusted R Square value of 0,840 or 84%, which means that the quality of the product and brand image contributes or influences purchasing decisions by 84% and the remaining 16% is influenced by other variables.